Further Discussion on Case Teaching Method Via A Case of Spreading False Information Online of Some Bad Vietnam Websites and Criminal Laws of Indonesian and China - Dinh Tran Ngoc Huy; Le Huong Hoa; Nguyen Trong Diep; Dinh Tran Ngoc Hien (RIRAI Publisher, 2022)
There will be suitable criminal laws for the case of spreading false information online of some bad Vietnam websites such as: Thanh nien newspaper, Tuoi tre newspaper, giaoduc.edu.vn, vietnamnet.vn, facebook.com> Liemchinhkhoahoc, nguyenduyxuan.net, etc. In specific, Thanh nien newspaper (Thanhnien.vn) and Tuoi tre newspaper (Tuoitre.vn) and recently, Vietnamnet.vn (online) violated during 2015-2022 period in Vietnam. By using synthesis and inductive methods, observations and experiences from other countries, authors will address this case that can be considered as internet crime (a kind of). Not only violating privacy law but also violating fake news publishing laws and slander laws. Allcott and Gentzkow (2017) worked toward a definition of “false news”. Their study defines this news genre as “A news story that has no factual basis, but it presented as news” . Hence, authors will both present a case teaching method for social sciences and law students (with English using) and address how Indonesia and China deal with this case. Then we also refer to Ho Chi Minh ideas on journalism to teach students in social sciences, and laws majors.